Time-domain variability properties of XTE J1650−500 during its 2001 outburst: evidence of disc–jet connection. Issue 4 (6th August 2020) - Chatterjee, Arka; Dutta, Broja G; Nandi, Prantik; Chakrabarti, Sandip K
ABSTRACT: The evolution of variability properties of Galactic transient sources is a diagnostic tool to understand various regimes of the accretion flow and its dynamics close to the central black hole. In this paper, we concentrate on the variability properties of the X-ray transient XTE J1650−500 and investigate the evolution of viscous delay, time lag, quasi-periodic oscillation (QPO) frequency, and their energy dependence throughout the rising phase as observed by Rossi X-ray Timing Explorer ( RXTE ) during its outburst in 2001. Our analysis reveals (1) a delay of 12 ± 1 d between 1 d-averaged hard (5–12 keV) and soft (1.5–3 keV) photon light curves as observed by RXTE /ASM; (2) QPOs with high rms values are observed in lower energy (4–8 keV) range; (3) the QPO frequencies and associated time lags were anticorrelated during the initial days of the rising phase, and later on, they were found to be correlated; (4) the time lags of Fe-line photons with respect to hard and soft photons remained almost constant during the initial days of hard state and the lag magnitude increased during the state transition. We perform comparative studies with outbursts of GX 339−4 and XTE J1550−564. We find the evolution of time lags associated with the QPO characteristics during the outburst – stronger QPOs at low energy and constant lags of broad Fe-line photons present a unique nature of outburst profile in XTE J1650−500. The possible cause of such variabilities is explained by considering disc–jet geometry closer to the central black hole.